Primer design for an accurate view of picocyanobacterial community structure by using high-throughput sequencing - Huber, Maria Paula (2019)
High-throughput sequencing (HTS) of the 16S rRNA gene has been used successfully to describe the structure and dynamics of microbial communities. Picocyanobacteria are important members of bacterioplankton communities, and, so far, they have predominantly been targeted using universal bacterial primers, providing a limited resolution of the picocyanobacterial community structure and dynamics. To increase such resolution, the study of a particular target group is best approached with the use of specific primers. Here, we aimed to design and evaluate specific primers for aquatic picocyanobacterial genera to be used with high-throughput sequencing. Since the various regions of the 16S rRNA gene have different degrees of conservation in different bacterial groups, we therefore first determined which hypervariable region of the 16S rRNA gene provides the highest taxonomic and phylogenetic resolution for the genera Synechococcus, Prochlorococcus, and Cyanobium. An in silico analysis showed that the V5, V6, and V7 hypervariable regions appear to be the most informative for this group. We then designed primers flanking these hypervariable regions and tested them in natural marine and freshwater communities. We successfully detected that most (97%) of the obtained reads could be assigned to picocyanobacterial genera. We defined operational taxonomic units as exact sequence variants (zero-radius operational taxonomic units [zOTUs]), which allowed us to detect higher genetic diversity and infer ecologically relevant information about picocyanobacterial community composition and dynamics in different aquatic systems. Our results open the door to future studies investigating picocyanobacterial diversity in aquatic systems.